Conceptual open space design of Március 15. square, Budapest - Varga, Dániel (4D Journal of Landscape Architecture and Garden Art, 2009)
The renewal of the city open spaces, as well as the reconsideration of the relationship between the abovementioned, is one of the most important tasks of the complex city rehabilitation. Reconsideration, which is needed in order to fulfil the modem people’s demands and requirements of a given city section. The city centrein Budapest is an emphasized scene of the city rehabilitation concept, nowadays. My thesis deals withthe redefinition of the open space architecture regarding one of the most outstanding elements in the city centre, that of the Március 15 Square. In doing the planning work, I was trying to give somé professional answers to the arisen questions regarding both the present usage necessities and the structures formed by history.
Keywords: Budapest; public space planning; Március 15. square